(untitled) (Tempo e Argumento, 2021)
The 20th century was characterized by major armed conflicts, two ("hot") World Wars and one Cold War, linked to military confrontations and revolutions in the South. During the 1970´s more than a dozen Revolutions in the Third World/Geopolitical South took place, from Nicaragua to Vietnam, and from Angola to Afghanistan. Most of them turned into conventional wars, namely, international military clashes, that lasted until the 1980s. The present article analyses the following cases: in Africa, Angola and Ethiopia, in the Middle East, Iran and Afghanistan, and, in Southeast Asia, Vietnam and Kampuchea/Cambodia. National liberation, social revolution and international geopolitical wars were closely intertwined in these changing conflicts, that branded Contemporary World History.